The effect of an upper respiratory care program on incidence of ventilator-associated pneumonia in mechanically ventilated patients hospitalized in intensive care units - Soheila Bakhtiari; Ahmadreza Yazdannik; Saeid Abbasi; Nasim Bahrami (Wolters Kluwer Medknow Publications, 2015)
Background: Ventilator-associated pneumonia (VAP) is a common side effect in patients with an endotracheal tube. This study aimed to evaluate the effect of an upper respiratory care program on the incidence of VAP in mechanically ventilated patients. Materials and Methods: In this clinical trial, 62 patients with endotracheal tube were selected and randomly allocated to intervention or control group. In the intervention group, an upper respiratory care program was performed and in the control group, routine care was done. Modified Clinical Pulmonary Infection Questionnaire was completed before, and on the third, fourth, and fifth day after intervention. Data were analyzed by repeated measure analysis of variance (ANOVA), chi-square, and independent t-test through SPSS 13. Results: The results of this study showed that until the fourth day, the incidence of VAP was similar in both intervention and control groups (P > 0.05), but on the fifth day, the incidence of VAP in the intervention group was significantly lower than in the control group (P < 0.05). Conclusions: The results of this study showed that in patients with an endotracheal tube, an upper respiratory care program may reduce the incidence of VAP. Therefore, in order to prevent VAP, nurses are recommended to perform this upper respiratory care program.